A new era in US-Indian security and defense relations? - Benjamin Schreer; Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2005)
For the United States, India is an essential cornerstone of the future security architecture in Asia. On June 28, 2005, the US Defense Minister Donald Rumsfeld and his Indian colleague, Pranab Mukherjee, signed the New Framework for the US-India Defense Relationship, which is supposed to put the security and defense relations of both countries on new footing. To what extent does this proclamation really mark a new 'era' in the American-Indian security relationship? What implications does this development have for European foreign and security policy? (SWP Comments / SWP)
Keywords: 320